Gender Differences in Risk Tolerance, Trust and Trustworthiness: Are They Related? - Stein T. Holden; Mesfin Tilahun (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2018)
The paper assesses risk tolerance, trust and trustworthiness among male and female youth group members in recently formed primary cooperative businesses in Ethiopia. Male members are found to be more risk tolerant, trusting and trustworthy than females. There is a strong positive correlation between individual risk tolerance and trust for male while this correlation is much weaker for female members. Individual risk tolerance is positively correlated with trustworthiness for males but not for females. Females are more trusting and trustworthy in groups with more risk tolerant members. Females' trustworthiness is more sensitive to group characteristics and experiences. The findings are consistent with social role theory as males appear more instrumental and females more communal in their responses.
Keywords: C93; D80; D81; D84; D90; 330; Gender differences; risk tolerance; trust; trustworthiness; youth business group members; social role theory; Ethiopia